Music Exhibitions in Local Settings – Sites of Cultural Memory? - Meyer, Andreas (Danish Yearbook of Musicology, 2024)
This paper deals with historically oriented museum displays in various West and Central European countries that focus on musical themes in local regions. Drawing on concepts and considerations of memory and heritage studies, I examine how local historical references are conveyed in these exhibitions and to what extent the latter can be seen as institutions promoting group identity. Jan Assmann’s distinction between communicative and cultural memory, according to which communicative memory is basedon everyday communication and refers to a rather recent past, while cultural memory focuses on events that happened further back in time, proves useful in this context. It turns out that there are many different ways of dealing with the past in the exhibitions and different forms of access, depending on the interests and prior knowledge of the visitors. Exhibitions on pop music themes support communicative memory in that the museum narratives encourage communication and thus promote cohesion. Regarding curatorial concepts and modes of reception, the formation of group identity seems to play a rather minor role in exhibitions on European art music. These exhibitions can still be regarded as sites of cultural memory, as they usually offer at least the opportunity to explore aspects of the (distant) history of one’s own group.